Research on Employee Recruitment: So Many Studies, So Many Remaining Questions - Breaugh, James A.; Starke, Mary (Journal of Management, 2000)
Over the last thirty years, the amount of research on recruitment topics has increased dramatically. Despite this increase, recent reviews of the recruitment literature often have had a somewhat pessimistic tone. Reviewers have concluded that we still do not know a great deal about why recruitment activities have the effects they do. In particular, recent reviews have criticized many of the studies conducted for being poorly designed, narrow in focus, and not grounded in theory. We believe that many of these criticisms are legitimate. We also believe that, in order for future studies to result in a better understanding of the recruitment process, such studies need to be designed with an appreciation of the complexity of the recruitment process (i.e., the number of variables involved and the nature of their relationships). In this regard, we offer an organizing framework of the recruitment process. In introducing this framework, we draw upon theories from a variety of research domains and give considerable attention to process variables (e.g., aplicant attention, message credibility, applicant self-insight) that mediate the relationships between recruitment activities (e.g., recruiter behavior) and recruitment outcomes (e.g., the number of applications generated). Having introduced an organizing framework, we selectively review recruitment research, giving particular attention to the topics of recruitment sources, recruiters, and realistic job previews. This review makes apparent a number of important issues that recruitment research has yet to address.